Using Microsoft Project 2010 - Atchison, Sonia (Que Pub., 2011)
More than just a book! Get comfortable with simple techniques that you can use to bring order to project management chaos. Don't just read about it: see it and hear it, with step-by-step video tutorials and valuable audio sidebars. Way more than just a book, this is all the help you'll ever need ... where you want, when you want! Learn Fast, Learn Easy! Using web, video, and audio Show Me video walks through tasks you've just got to see - including bonus advanced techniques Tell Me More audio delivers practical insights straight from the experts Let Me Try It tasks break down the complex into easy-to-follow, step-by-step sequences.